Effects of trypanosomiasis on productivity of East African Zebu cattle exposed to drug resistant trypanosomes - Mulatu, W.; Rowlands, G.J.; D'Ieteren, G.D.M.; Nagda, S.M. (OAU/STRC, 1995)
Research has been undertaken since 1986 in the Ghibe valley, southwest Ethiopia, monitoring approximately 840 village East African Zebu cattle monthly to assess the effects of trypanosomiasis on productivity. The average monthly trypanosome prevalence between 1986 and 1989 was about 30 percent. Many cases of parasitaemia that were treated were found parasitaemic again the following month, pointing to the possible existence of drug resistance; this was confirmed in the laboratory with all trypanosome isolates tested showing resistance to diminazene aceturate. With such a high incidence of drug resistance, a higher monthly trypanosome prevalence might have been expected in the village cattle. Thus, whilst treatment was not eliminating infections, it may have helped to limit the trypanosome growth and allowed the cattle to maintain reasonable levels of health and productivity. This was confirmed by statistical analysis of the productivity data. Although there were statistically significant effect of trypanosomiasis appeared to be on calf and foetal mortality, particularly during periods of very high tsetse challenge or increased trypanosomiasis risk brought about by other stress-related factors.